2021
DOI: 10.1037/pag0000604
|View full text |Cite
|
Sign up to set email alerts
|

“I felt so old this morning.” Short-term variations in subjective age and the role of trait subjective age: Evidence from the ILSE/EMIL ecological momentary assessment data.

Abstract: Subjective age, how old people feel compared to their chronological age, is a central indicator of age identity and highly predictive for developmental outcomes. While mostly used as a trait-like concept in previous research, recent studies employing experimental designs and daily assessments suggest that subjective age can vary after experimental manipulations or between days. However, less is known about whether subjective age varies over even shorter time frames such as within moments on a given day, how su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
18
1
1
Order By: Relevance
“…At the within-person level, momentary subjective age and perceived stress correlated at r = .09 ( p < .001), subjective age and cortisol correlated at r = .04 ( p = .007), and perceived stress and salivary cortisol correlated at r = .05 ( p < .001). As previously reported (Kornadt et al, 2021), around a quarter of the variability of momentary subjective age was attributable to within-person variability (ICC = .73). 4 For cortisol (after controlling for Level 1 confounders), 75% of variability was attributable to within-person variability (ICC = .25), and 65% for perceived stress (ICC = .35).…”
Section: Preliminary and Descriptive Analysessupporting
confidence: 77%
See 3 more Smart Citations
“…At the within-person level, momentary subjective age and perceived stress correlated at r = .09 ( p < .001), subjective age and cortisol correlated at r = .04 ( p = .007), and perceived stress and salivary cortisol correlated at r = .05 ( p < .001). As previously reported (Kornadt et al, 2021), around a quarter of the variability of momentary subjective age was attributable to within-person variability (ICC = .73). 4 For cortisol (after controlling for Level 1 confounders), 75% of variability was attributable to within-person variability (ICC = .25), and 65% for perceived stress (ICC = .35).…”
Section: Preliminary and Descriptive Analysessupporting
confidence: 77%
“…One might consequently also expect a lower coupling between cortisol and subjective age in older individuals with poor rather than good physical health or cognitive functioning. Furthermore, in the current data set, people with younger trait subjective ages tended to vary more in their momentary subjective age ratings, presumably because of a more flexible mindset for what aging means (Kornadt et al, 2021). In addition, HPA axis functioning as well as age-related experiences and their interaction also differ between men and women.…”
Section: The Role Of Age and Other Potentially Influential Variablesmentioning
confidence: 65%
See 2 more Smart Citations
“…More recently, results of an ecological momentary assessment study indicated that subjective age can vary from momentto-moment within a day, with similar degrees of variability observed among young-old and old-old adults (70). Studies have also shown that daily stressor exposure is related to daily felt age among older adults not exposed to higher levels of negative life events (71), and that higher daily AARC-losses is associated with higher daily negative affect (5).…”
Section: Between-and Within-person Associations Of Awareness Of Age-r...mentioning
confidence: 90%